A study on arrival time corrections by using extender and bender elements. Issue 4 (September 2015) - Cherian, A. C.; Kumar, J.
<x content-type="archive" xml:space="preserve">Abstract</x> The arrival times of primary (P) and shear (S) waves in dry sand were measured by using extender and bender elements. A series of laboratory tests were performed at five different frequencies, varying between 1 and 10 kHz, in loose and dense sands for three different confining pressures. While determining the times of arrival of both P- and S-waves, two corrections were applied to incorporate (i) the presence of an initial offset in the input signal and (ii) the time lag because of an existence of peripheral electronics between the input and received signals when the source and receiver elements are kept in direct contact with each other. The absolute magnitude of the resultant of these two corrections was found to reduce with an increase in the frequency of the input signal. The determination of the P-wave arrival time does not pose any serious difficulty. It has been noted that it becomes equally accurate to measure the arrival times of the S-wave provided the proposed two corrections are incorporated.